Pre-Activation of Toll-Like Receptor 2 Enhances CD8+ T-Cell Responses and Accelerates Hepatitis B Virus Clearance in the Mouse Models - Lin, Yong; Huang, Xuan; Wu, Jun; Liu, Jia; Chen, Mingfa; Ma, Zhiyong; Zhang, Ejuan; Liu, Yan; Huang, Shunmei; Li, Qian; Zhang, Xiaoyong; Hou, Jinlin; et al. (Frontiers in Immunology, 2018)
Toll-like receptors (TLRs) play a crucial role in activation of innate immunity, which is essential for inducing effective adaptive immune responses. Our previous studies have shown that toll-like receptor 2 (TLR2) is required to induce effective virus-specific T-cell responses against hepatitis B virus (HBV) in vivo. However, the contribution of TLR2 activation to adaptive immunity and HBV clearance remains to be clarified. In this study, we explored the hydrodynamic injection (HI) mouse models for HBV infection and examined how the TLR2 agonist Pam3CSK (P3C) influences HBV control and modulates HBV-specific T-cell response if applied in vivo. We found that TLR2 activation by P3C injection leads to the rapid but transient production of serum proinflammatory factors interleukin-6 and tumor necrosis factor-α and activation of CD8+ T cells in vivo. Then, the anti-HBV effect and HBV-specific T-cell immunity were investigated by TLR2 activation in the mouse models for persistent or acute HBV infections using HBV plasmids pAAV-HBV1.2 and pSM2, respectively. Both P3C application at early stage and pre-activation promoted HBV clearance, while only TLR2 pre-activation enhanced HBV-specific T-cell response in the liver. In the mouse model for acute HBV infection, P3C application had no significant effect on HBV clearance though P3C significantly enhanced the HBV-specific T-cell response. Collectively, TLR2 pre-activation enhances HBV-specific T-cell responses and accelerates HBV clearance in HI mouse models. Thus, the modulation of host immune status by TLR2 agonists may be explored for immunotherapeutic strategies to control HBV infection.